Balancing Mechanical Properties, Water Resistance, and Soil Degradability of Rice Flour/CMC-Based Biodegradable Drinking Straws - Alya Keisha Intan Chayrunisya; Qanitah Nibras Firmaniya; Srie Muljani; Luluk Edahwati; Caecilia Pujiastuti (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The development of biodegradable drinking straws requires a balance between mechanical integrity, flexibility, water resistance, and post-use degradability. This study investigated the effects of rice flour-to-carboxymethyl cellulose (CMC) ratio and plasticizer conditions on the functional performance of biodegradable drinking straws. Five rice flour:CMC ratios (1:3, 1.5:2.5, 2:2, 2.5:1.5, and 3:1) were combined with two plasticizers (glycerol and sorbitol) at three loadings (1.5, 2.0, and 3.0 mL), resulting in 30 formulations. The resulting straws were evaluated for tensile strength, elongation at break, water resistance, and soil-burial degradation. Tensile strength ranged from 0.588 to 3.822 MPa, with the highest value obtained at a rice flour : CMC ratio of 1:3 containing 1.5 mL sorbitol. Elongation at break ranged from 12.545 to 88.964%, with the maximum achieved at a ratio of 3:1 containing 2.0 mL glycerol, demonstrating a clear strength–flexibility trade-off. Water resistance varied from 25 to 74%, while soil-burial mass loss reached 86.2–100% after 21 days. The different formulations maximizing tensile strength, flexibility, and water resistance indicate that plasticizer performance is strongly dependent on matrix composition rather than plasticizer identity alone.